THEORETICAL ANALYTICAL METHOD OF CUTTING FORCES IN TURNING OF Al/Si C COMPOSITES BASED ON THREE DEFORMATION AREA - PENG ChunLei (Jixie qiangdu)
To predict the cutting force of cutting Si C particle reinforced aluminum-based compositeaccurately,an innovative theoreticalanalytical method is proposed in consideration of the influence of Si C particles on aluminum substrate. This method is built on the orthogonal cutting model,cutting force is considering to derive from threedeformed zones,namely,primary shear zone,primary friction zone andplough zone. Shear force,sliding and rolling friction force and plough force is analyzed based on the three deformation area,which is decomposed in X,Y,Z direction. To verify the validity of this method,turning experiments on 50% particles Si Cp/Al composites are conducted on CA6140 A turning-lathe by using PCD cutting tool. Experimental results show that the analytical methodcan be used to predict the cutting force accuratelyon the conditions of some cutting parameters.